Hapten designs based on aldicarb for the development of a colloidal gold immunochromatographic quantitative test strip - Shen, Hong; Wan, Yuping; Wu, Xiaosheng; Zhang, Yu; Li, Jingwen; Cui, Tingting; Sun, Han; Cui, Haifeng; He, Kailun; Hui, Guangpeng; Chen, Xu; Liu, Guoqiang; et al. (Frontiers in Nutrition, 2022)
The common carbamate insecticide aldicarb is considered one of the most acutely toxic pesticides. Herein, rational design was used to synthesize two haptens with spacers of different carbon chain lengths. The haptens were then used to immunize mice. The antibodies obtained were evaluated systematically, and a colloidal gold immunochromatographic strip was developed based on an anti-aldicarb monoclonal antibody. The 50% inhibition concentration and linear range of anti-aldicarb monoclonal antibody immunized with Hapten 1 were 0.432 ng/mL and 0.106–1.757 ng/mL, respectively. The cross-reactivities for analogs of aldicarb were all <1%. The limit of detection of the colloidal gold immunochromatographic strip was 30 μg/kg, and the average recoveries of aldicarb ranged from 80.4% to 110.5% in spiked samples. In the analysis of blind samples, the test strip could accurately identify positive samples detected by the instrumental method in the GB 23200.112-2018 standard but produced some false positives for negative samples. This assay provides a rapid and accurate preliminary screening method for the determination of aldicarb in agricultural products and environments.